Effect of adipocyte-derived IGF-I on adipose tissue mass and glucose metabolism in the Berlin Fat Mouse. (4th March 2018) - Hesse, Deike; Trost, Jan; Schäfer, Nadine; Schwerbel, Kristin; Hoeflich, Andreas; Schürmann, Annette; Brockmann, Gudrun A.
Abstract: Besides liver, IGF-I is expressed in adipose tissue. However, the effects of this local IGF-I on adipose tissue and metabolism are unclear. We generated adipocyte-specific knock-out mice on the background of the Berlin Fat Mouse Inbred (BFMI) line to evaluate the contribution of adipocyte-IGF-I on glucose metabolism and adipose tissue development. BFMI mice are obese, non-diabetic with elevated plasma insulin and IGF-I concentration. The knock-out in adipocytes led to a total white adipose tissue expression of 50–60% due to unaltered Igf-1 expression in stromavascular cells. The lack of IGF-I from adipocytes did not alter plasma IGF-I concentration. BFMI Chr3 -Igf-I-KO Q-AT mice had reduced adipose tissue mass in most depots. During oral glucose tolerance tests, BFMI Chr3 -Igf-I-KO Q-AT mice showed an impaired glucose clearance ( p  = .03). Interestingly, insulin action was enhanced during insulin tolerance tests ( p  = .05). In conclusion, adipocyte-specific IGF-I ablation in obese BFMI mice results in reduced adipose tissue mass and thereby alters glucose metabolism.